Routing in wireless sensor networks - Rachid, Ennaji; Mohammed, Boulmalf (2009 International Conference on Multimedia Computing and Systems, 2009)
A sensor network is a system that consists of thousands of very small stations called sensor nodes. The main function of sensor nodes is to monitor, record, and notify a specific condition at various locations to other stations and end users. Eventually, this presents a wide range of applications that motivates research in sensor networks. The communication among nodes is done in a wireless fashion, and thus, the name of wireless sensor networks. This paper studies wireless sensor networks throughout a number of selected articles, papers, and online resources. A good understanding of sensor networks and wireless communications is the main learning outcome of this study. Specifically, the research concentrates on routing in sensor networks, and is supported by a simulation of a sensor network application performed with network simulator. Before simulating, a careful study of available simulators is conducted as …
Keywords: Wireless Sensor Networks; Routing; Simulation; Network Simulator